Gerakan Literasi Sekolah Mempengaruhi Kemampuan Siswa Kelas IV SDN Kletekan 2 dalam Menulis Puisi - Ari Wibowo; Uci Ulfa Nur Afifah; Novia Rahma Rista Utami (LP. Ma'arif Janggan Magetan, 2024)
The School Literacy Movement (GLS) is a government initiative aimed at fostering reading interest and literacy culture among students. One crucial element of literacy is writing ability, including poetry writing. This study aims to examine the impact of GLS on students' poetry writing skills. Literacy encompasses not only reading skills but also writing skills. Poetry writing is an important form of creative expression in literacy education. Poetry helps students develop language skills, enrich their vocabulary, and express their emotions and thoughts. This research aims to determine whether the school literacy movement can influence the poetry writing skills of students at SDN Kletekan 2. The approach in this study is quantitative, with a one-group pre-test post-test research design. The sample consists of all 15 fourth-grade students at SDN Kletekan 2. The prerequisite tests for the study include normality and homogeneity tests, where data is considered normally distributed if the significance value (sig) is > 0.05. The sample is considered homogeneous if the significance value (sig) is > 0.05. Prerequisite tests were conducted using the SPSS 24 application. This study employs hypothesis testing with a paired sample t-test. Data collection was conducted using test instruments. The results indicate that the school literacy movement activities have an impact on the poetry writing skills of fourth-grade students at SDN Kletekan 2, as shown by the paired sample t-test results with a significance value of 0.000 < 0.05. Thus, it can be concluded that the school literacy movement activities can influence the poetry writing skills of fourth-grade students at SDN Kletekan 2.